Giving Baby Porridge Made From Moringa Leaves and Snakehead Fish to Toddlers in Yogyakarta Indonesia - Fitriahadi, Enny; Rosida, Luluk; Syagata, Anindhita Syahbi; Makbul, Ika Aida Aprilini binti; Intarti, Wiwit Desi (Jurnal Kesehatan Masyarakat, 2024)
Problems in toddlers who are inadequate in consuming MP-ASI cause one of them is stunting. Stunting is a major health problem in communities in developing countries. The purpose of this study was to determine the effect of providing MPASI baby porridge made from moringa leaves and snakehead fish on body weight. The research method used This study design used a randomized controlled trial (RCT) which investigated the effect of providing MPASI baby porridge made from moringa leaves and snakehead fish on toddler body weight. The sample size calculated was 30 respondents. The sample size of 30 toddlers aged 1-12 months was divided into 15 toddlers who were given treatment and 15 toddlers who were not given treatment. The results showed that the percentage of toddlers with underweight in the intervention group decreased from a mean of 6513.33 to 6706.67 while in the control group it only decreased from a mean of 6500.00 to 6586.67. Overall, the weight status of toddlers in the intervention group changed significantly (p 0.000).